Microneedles for diagnosis and therapeutic drug monitoring - Thean, Jia Hui (2018)
The first invention of glucose biosensor was made by Leland Clark in the mid of 20th century. He was considered as the ‘father of biosensor’ due to his discovery of the fundamental principal of a glucose biosensor, which is widely used today for diabetic diagnosis. A variety of glucose sensing devices have been introduced to the market nowadays with the aim of efficiently monitoring glucose level in a convenient, low cost and least uncomfortable feeling way. This study investigates the reliability used of paper-based MeHA microneedle patches penetrating through the agarose gel to detect the presence of glucose. The microneedles were fabricated with addition of the polymer MeHA into the casted PDMS mold. A solution containing enzymes and color indicators for glucose detection was prepared and coated on nitrocellulose paper. The paper was immediately attached on the dried microneedle patch due to the good hydrophilicity of the MeHA for better adhesion. The fabrication of microneedle was followed by the characterization on its mechanical strength. The MeHA microneedle used in this project exhibits its capability in sustaining its structural integrity under the execution of 0.1N, which is the insertion force to the skin. The colorimetric detection of glucose substance with MeHA microneedle was analysed by converting the R, G, B form of data into saturation and value. Results showed that the saturation and value vary along with the glucose concentration present in the environment. This technology can be further advanced by investigating its multi-analyte capability, specificity and cell cytotoxicity to establish a reliable, safe and convenient biosensor in the future.